2023
DOI: 10.3390/toxics11020100
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Polystyrene Microplastic Fragments Has No Effect on Honey Bee Survival, but Reduces Feeding Rate and Body Weight

Abstract: Microplastics (MPs), in the form of fragments and fibers, were recently found in honey samples collected in Ecuador as well as in honey bees collected from Denmark and China. However, little is known about how MPs impact bee health. To fill this knowledge gap, we investigated the potential toxicity of irregularly shaped polystyrene (PS)-MP fragments on honey bee health. In the first experiment of its kind with honey bees, we chronically exposed bees with a well-established gut microbiome to small (27 ± 17 µm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…MPs are readily absorbed into plants from the soil 80 , and bee bodies through contaminated food under laboratory conditions 81 ; they can also absorb pollutants such as pesticides acting as a source and sink of environmental contaminants 82 . MPs can increase honey bee mortality (albeit only at high concentrations 83 ), decrease feeding rate and body weight 84 , change the diversity of gut biota and gene expression related to oxidative damage, detoxification, and immunity, and increase worker susceptibility to antibiotics 82 . MPs likely interact with other environmental stressors, and co-occurrences are highly likely in agricultural landscapes; for example, honey bees showed higher mortality to viral infection when exposed to MPs 85 .…”
Section: Resultsmentioning
confidence: 99%
“…MPs are readily absorbed into plants from the soil 80 , and bee bodies through contaminated food under laboratory conditions 81 ; they can also absorb pollutants such as pesticides acting as a source and sink of environmental contaminants 82 . MPs can increase honey bee mortality (albeit only at high concentrations 83 ), decrease feeding rate and body weight 84 , change the diversity of gut biota and gene expression related to oxidative damage, detoxification, and immunity, and increase worker susceptibility to antibiotics 82 . MPs likely interact with other environmental stressors, and co-occurrences are highly likely in agricultural landscapes; for example, honey bees showed higher mortality to viral infection when exposed to MPs 85 .…”
Section: Resultsmentioning
confidence: 99%
“…However, honey bees were unable to differentiate the contaminated solution, which could make them prone to chronic effects of MPs in longterm consumption. Al Naggar et al [115] reported that chronic exposure to polystyrene MPs at lower doses (10-100 µg/L) lowered the feeding rate and body weight of honey bees, however, the survival rate was not influenced. These effects can relate to not only the dose and type but also the size of plastic particles [111].…”
Section: Microplastics (Mps)mentioning
confidence: 99%
“…10 Additionally, microplastics have been found in honeybee-derived products, such as honey. 18,19 The negative electric charge of microplastics is similar to that of pollen grains; therefore, microplastics may attracted to pollinators after grooming, 20 substituting for the pollen loads carried by pollinators. 21 Microplastic carrying pollinators 10 and airbone microplastics 22,23 might result in the deposition of plastic fragments on flowers, 4,5,24 different plant species) interferes in pollen−pistil interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, a field study on the honeybee Apis mellifera, which is one of the most conspicuous and globally important pollinators, revealed the presence of microplastic in the bee body, including in individuals from pristine sites . Additionally, microplastics have been found in honeybee-derived products, such as honey. , The negative electric charge of microplastics is similar to that of pollen grains; therefore, microplastics may attracted to pollinators after grooming, substituting for the pollen loads carried by pollinators . Microplastic carrying pollinators and airbone microplastics , might result in the deposition of plastic fragments on flowers, ,, blocking stigmatic surfaces for pollen tube development and decreasing seed production in a way to similar to how heterospecific pollen (the pollen from a different plant species) interferes in pollen–pistil interactions. As pollination involves seed and fruit production, microplastics might be a threat to food yield.…”
Section: Introductionmentioning
confidence: 99%